2018
DOI: 10.1093/pasj/psy088
|View full text |Cite
|
Sign up to set email alerts
|

An application of the Ghosh & Lamb model to the accretion-powered X-ray pulsar X Persei

Abstract: The accretion-induced pulse-period changes of the Be/X-ray binary pulsar X Persei were investigated over a period of 1996 January to 2017 September. This study utilized the monitoring data acquired with the RXTE/ASM in 1.5-12 keV and MAXI/GSC in 2-20 keV. The source intensity changed by a factor of 5-6 over this period. The pulsar was spinning down for 1996-2003, and has been spinning up since 2003, as already reported. The spin up/down rate and the 3-12 keV flux, determined every 250 d, showed a clear negativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…In the case of wind-capture accretion in supergiant high-mass X-ray binaries, Corbet & Krimm (2013) discussed the relation between their modulation and the geometry of binary systems and determined that the superorbital period is proportional to the binary orbital period. In contrast, as claimed by Yatabe et al (2018), X Per has a disk accretion scheme similar to that of the other Be/X-ray binaries. Thus, the variation of the mass-transfer rate from a circumstellar disc to a neutron star is the cause of the periodic superorbital modulation.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the case of wind-capture accretion in supergiant high-mass X-ray binaries, Corbet & Krimm (2013) discussed the relation between their modulation and the geometry of binary systems and determined that the superorbital period is proportional to the binary orbital period. In contrast, as claimed by Yatabe et al (2018), X Per has a disk accretion scheme similar to that of the other Be/X-ray binaries. Thus, the variation of the mass-transfer rate from a circumstellar disc to a neutron star is the cause of the periodic superorbital modulation.…”
Section: Discussionmentioning
confidence: 75%
“…X Persei (X Per or 4U 0352+309) is a classical persistent Be/X-ray binary composed of a slowly rotating X-ray pulsar (P spin ∼ 835 second; Yatabe et al 2018) and (09.5III-B0Ve) optical companion (HD 24534;Lyubimkov et al 1997). This source was independently discovered by Ariel 5 and Copernicus (White et al 1976).…”
Section: Long-term X-ray and Optical Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate estimates of the surface MF of accreting NSs are available through detections of cyclotron resonance scattering features (CRSFs) in their X-ray spectra (Makishima 2016). However, the current observational sensitivity limits the CRSF detections to < ∼ 100 keV, and hence B < ∼ 10 13 G. As an alternative method to estimate the dipole component of B (particularly towards higher values) of accreting NSs, the classical accretion torque theory by Ghosh and Lamb (1979), hereafter GL79, has been revived, calibrated, and applied to several high-mass X-ray binaries (HMXBs) (Takagi et al 2016;Makishima 2016;Sugizaki et al 2017;Yatabe et al 2018;Sugizaki et al 2020). In particular, Yatabe et al (2018) studied X Persei, the HMXB which has an NS companion with a long spin period (∼835 s) in an approximate torque equilibrium, a low luminosity (∼10 35 erg s −1 ), and a hard continuum extending to ∼ 80 keV without a clear cutoff.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current observational sensitivity limits the CRSF detections to < ∼ 100 keV, and hence B < ∼ 10 13 G. As an alternative method to estimate the dipole component of B (particularly towards higher values) of accreting NSs, the classical accretion torque theory by Ghosh and Lamb (1979), hereafter GL79, has been revived, calibrated, and applied to several high-mass X-ray binaries (HMXBs) (Takagi et al 2016;Makishima 2016;Sugizaki et al 2017;Yatabe et al 2018;Sugizaki et al 2020). In particular, Yatabe et al (2018) studied X Persei, the HMXB which has an NS companion with a long spin period (∼835 s) in an approximate torque equilibrium, a low luminosity (∼10 35 erg s −1 ), and a hard continuum extending to ∼ 80 keV without a clear cutoff. The application of the GL79 modeling has shown that the NS in X Persei has B ∼10 14 G, which is significantly higher than those of ordinary X-ray pulsars, and is comparable to those of magnetars.…”
Section: Introductionmentioning
confidence: 99%